2021
DOI: 10.1097/md.0000000000026136
|View full text |Cite
|
Sign up to set email alerts
|

Admixed phenotype of NEDD4L associated periventricular nodular heterotopia

Abstract: Rationale: Periventricular nodular heterotopia-7 (PVNH7) is a neurodevelopmental disorder associated with improper neuronal migration during neurogenesis in cortex development caused by pathogenic variants in the NEDD4L gene. Patient concerns: We report the case of a polystigmatized 2-year-old boy having significant symptomatologic overlap with PVNH7, such as delayed psychomotor and mental development, seizures and infantile spasms, periventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…After reviewing data from previously reported cases (Broix et al, 2016 ; Elbracht et al, 2018 ; Kato et al, 2017 ; Pecimonova et al, 2021 ; Stouffs et al, 2020 ), we observed that nearly all 15 patients (seven male, eight female) in the 11 reported families presented with psychomotor retardation, hypotonia, and variable degrees of syndactyly (usually second/third toe). Among them, 53% also exhibited cleft palate, while 46% experienced seizures.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…After reviewing data from previously reported cases (Broix et al, 2016 ; Elbracht et al, 2018 ; Kato et al, 2017 ; Pecimonova et al, 2021 ; Stouffs et al, 2020 ), we observed that nearly all 15 patients (seven male, eight female) in the 11 reported families presented with psychomotor retardation, hypotonia, and variable degrees of syndactyly (usually second/third toe). Among them, 53% also exhibited cleft palate, while 46% experienced seizures.…”
Section: Discussionmentioning
confidence: 86%
“…After reviewing data from previously reported cases (Broix et al, 2016;Elbracht et al, 2018;Kato et al, 2017;Pecimonova et al, 2021;Stouffs et al, 2020), we observed that nearly all 15 patients (seven male, eight female) in the…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations